2013
DOI: 10.1002/eat.22149
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel phenotypes of vulnerability and resistance to activity‐based anorexia in adolescent female rats

Abstract: Objective Activity-based anorexia is a translational rodent model that results in severe weight loss, hyperactivity, and voluntary self-starvation. The goal of our investigation was to identify vulnerable and resistant phenotypes of activity-based anorexia in adolescent female rats. Method Sprague-Dawley rats were maintained under conditions of restricted access to food (N = 64; or unlimited access, N = 16) until experimental exit, predefined as a target weight loss of 30–35% or meeting predefined criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Our results add support to the hypothesis that RW activity during ad-libitum feeding has predictive value for body weight changes during ABA in female rats and extend this result to male rats (Figure 4 and 5). Human studies suggest that pre-morbid BW correlates with the severity of body weight loss during AN [57] and linear analysis of ABA susceptibility suggest it can contribute to accuracy of prediction of ABA weight loss [18, 25, 26]. Overall, our results align with previous data suggesting that body weight and RW activity during ad-libitum food intake contribute to susceptibility to weight loss in ABA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results add support to the hypothesis that RW activity during ad-libitum feeding has predictive value for body weight changes during ABA in female rats and extend this result to male rats (Figure 4 and 5). Human studies suggest that pre-morbid BW correlates with the severity of body weight loss during AN [57] and linear analysis of ABA susceptibility suggest it can contribute to accuracy of prediction of ABA weight loss [18, 25, 26]. Overall, our results align with previous data suggesting that body weight and RW activity during ad-libitum food intake contribute to susceptibility to weight loss in ABA.…”
Section: Discussionsupporting
confidence: 90%
“…The best predictive model was a combination of RW activity during ad-libitum feeding, SPA and body weight history (Figures 4 and 5). Previous studies of ABA susceptibility showed that RW activity is a strong predictor of body weight loss during ABA in female rats [18, 25, 26]. Our results add support to the hypothesis that RW activity during ad-libitum feeding has predictive value for body weight changes during ABA in female rats and extend this result to male rats (Figure 4 and 5).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent, elegant studies to determine what underlying factors lead animals to be susceptible to the development of ABA have laid the groundwork for the utility of the ABA model in prevention and treatment studies that will be applicable to human disease. 32 …”
Section: Introductionmentioning
confidence: 99%
“…The other is voluntary food restriction, as the food restricted animals paradoxically begin to choose exercise over feeding, even during the period of food access. When the ABA-inducing environment is imposed upon adolescent female rats, this combination of behaviors leads to severe body weight loss and mortality, unless removed from the ABA-inducing environment by around the fifth day (Routtenberg and Kuznesof, 1967, Barbarich-Marsteller et al, 2013, Chowdhury et al, 2013, Gutierrez, 2013). Adolescent female rats placed in an ABA-inducing environment for four days exhibit a 500% greater level of non-synaptic α4βδ−GABA A receptors (α4βδ−GABA A Rs) at dendritic spines of CA1 pyramidal cells, relative to controls (Aoki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%